Socialization on the use of medicinal plants to raise public awareness of herbal medicine - Faruk Jayanto Kelutur; Syilvi Adini; Riffa Sephillda Amoretti; Siti Laila Rohmah; Indah Ayu Nur Hasana; Andri Harpan; Agriyaningsih Oktaviana Hadi (University of Merdeka Malang, 2025)
Over time, advancements in the medical field have led to a decline in public trust in herbal medicine due to the fast-acting effects of chemical drugs. However, herbal medicines generally have fewer side effects. Public awareness of health remains low, particularly in Kamanisan Village, largely due to limited knowledge. A comprehensive strategy is needed to enhance public awareness and understanding of medicinal plants. This program aims to increase public knowledge and awareness of the use of medicinal plants. The activity took place in RT.07/RW.13 Kamanisan, Curug District, involving 30 participants. It included a pre-test questionnaire, material presentation, Q&A session, and post-test. The results showed an increase in participant knowledge from 86.76 percent to 90 percent. The number of participants who strongly agreed with the use of medicinal plants (in Indonesia: TOGA) rose from 12 to 22 people. The Chi-Square test indicated a significant impact on knowledge and attitudes before and after the session. Additionally, the paired sample t-test confirmed differences in pre- and post-knowledge, pre- and post-attitude, and knowledge-to-attitude shifts. The success of this activity strengthens public awareness of TOGA as a complementary and alternative treatment for various diseases.